Understanding the Barriers and Facilitators of Digital Health Technology (DHT) Implementation in Neurological Rehabilitation: An Integrative Systematic Review - Kathryn Jarvis; Clare Thetford; Edward Turck; Kelly Ogley; Rachel C Stockley (SAGE Publishing, 2024)
Background: Digital Health technologies (DHT) have potential to deliver intensive, novel and engaging rehabilitation for people with neurological conditions, yet health services lack a strong track record in embedding DHT into practice. The aim of this review was to synthesise factors that have been shown to influence implementation of DHT into neurological rehabilitation. Method: An integrative review was undertaken. An extensive search of MEDLINE, CINAHL, AMED, EMBASE was undertaken. The title and abstract of all retrieved sources were screened against pre-defined criteria. Retained sources underwent full text review. The quality of all included sources was assessed. A meta-ethnographic synthesis explored commonalities and contradictions of the included studies. Results: Fourteen studies (1 quantitative, 8 qualitative and 5 mixed methods) were included. Eleven implementation theories/models/frameworks were used across the 14 studies. Five themes were identified: (i) individual factors; (ii) user experience of the technology; (iii) the content of the intervention; (iv) access to the technology and (v) supporting use. Conclusions: Key factors which appear to influence the implementation of DHT into clinical settings are highlighted. Implementation theories, models and frameworks are under-utilised in DHT rehabilitation research. This needs to be addressed if DHT are to realise their potential in neurological rehabilitation. Registration: The protocol was registered and is available from PROSPERO (CRD42021268984).